Oligodeoxynucleotide probes for Campylobacter fetus and Campylobacter hyointestinalis based on 16S rRNA sequences. - Wesley, I V (1991)
Deoxyoligonucleotide probes were constructed for the identification of Campylobacter fetus and Campylobacter hyointestinalis based on 16S rRNA sequence data. Probes were targeted to hypervariable regions of 16S rRNA. Specificity of oligonucleotide probes was tested in a colony blot assay with type strains of 15 Campylobacter and Arcobacter species as well as in a slot blot format using genomic DNA extracted from field strains of C. fetus and C. hyointestinalis. Two oligonucleotides were constructed for C. fetus that hybridized with equal specificity with each of 57 biochemically confirmed isolates of C. fetus but not with any other Campylobacter species. The C. hyointestinalis probe reacted with 47 of 48 biochemically confirmed field isolates of C. hyointestinalis. In Southern blot hybridization of BglII digests of genomic DNA, the respective probes reacted within three restriction fragments of either C. hyointestinalis (7.2, 8.2, and 10.1 kb) or C. fetus (7.0, 7.7, and 9.0 kb). This suggests multiple copies of genes encoding 16S rRNA.